Changing incentives for early retirement - Causal evidence from a cohort based pension reform - Johannes Geyer; Barbara Engels; Peter Haan (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper we exploit a cohort specific pension reform to estimate the causal employment effect of changes in the financial incentives to retire. In particular we analyze the effect of the introduction of pension deductions for early retirement on female employment. For the empirical analysis we use high-quality administrative data from the German Federal Pension Insurance (VSKT) and find positive and significant effects of the reform on employment.
Keywords: J18; J26; J14; 330